3D macro- and microfabric analyses of Neoproterozoic diamictites from the Valjean Hills, California (United States) - Kettler, C.; Phillips, E.; Pichler, K.; Smrzka, D.; Vandyk, T. M.; Le Heron, D. P. (Frontiers in Earth Science, 2023)
The Cryogenian interval (720–635 Ma) is famous for a rich archive of diamictites, many of which were deposited during glaciations. Classic examples are exposed in the Kingston Peak Formation of the Valjean Hills, near Death Valley (United States), with previous work pointing to multiple glacial cycles in other outcrop belts. Within any glacial period, diamictites are widespread, and in addition, their mechanics of deposition are highly variable. Some are massive in appearance at outcrop or in hand specimens and apparently lack any information that allows their mode of emplacement to be elucidated. Yet, the correct interpretation for deep-time successions in this area is especially important, since it is debated whether the diamictites are either associated with a tectonically driven origin, associated with rifting at the south-western Laurentian margin alongside slope-controlled gravitational mass movement, or predominantly deposited as (sub)glacial diamictites. In this paper, we demonstrate how diamictite texture can be objectively quantified based on clast orientations, at both macroscale and microscale (micromorphology), guiding interpretations. Our method is based on a technique used for Quaternary sediments, by mapping the apparent longest axes of skeleton grains (ranging from fine-grained sand to fine-grained pebbles) in oriented thin sections and reconstructing their microfabric in a 3D space coupled with macrofabric data for each diamictite. In this way, we could identify a bimodal signal in the orientation of the longest axes for each sample. Evidence for shearing and soft sediment deformation supports either subaqueous or subglacial deposition with deformation induced by basal sliding with a paleoflow directed toward the southeast. Our combined approach of micro- and macrofabric analyses can also encourage acquiring accurate fabric data for seemingly structureless diamictites from other deep-time rock archives in an objective manner.